EVALUASI IMPLEMENTASI PROGRAM BANTUAN OPERASIONAL SEKOLAH PADA SATUAN PENDIDIKAN SEKOLAH DASAR NEGERI TAHUN 2019-2020 DI KECAMATAN LUBUK BASUNG - Wilda Sumarsyah (Universitas Muhammadiyah Bengkulu, 2021)
Evaluation Policy implementation is a process to see how the process of implementing a policy has been implemented or to see whether the process of implementing a policy has been implemented in accordance with predetermined technical or implementation instructions. One of the programs from the government is the BOS program. The background of the BOS program was the increase in fuel prices which resulted in a decrease in people's purchasing power which had a negative impact on poor people's access to Nine Years of Basic Education. This study finds out about the evaluation of the implementation of the school operational assistance program in the state primary school education unit 2019-2020 in Lubuk Basung sub-district. This research uses implementation evaluation theory according to Grindle. This research uses a qualitative approach with a descriptive type. The selection of informants was carried out by using purposive sampling technique. Meanwhile, data analysis was carried out ethically and emotionally. Based on the results of the research that has been carried out, the researcher draws the conclusion that the evaluation of the implementation of the school operational assistance program in the 2019-2020 public elementary school education unit in Lubuk Basung sub-district has been carried out well even